Model Forest and Land Fires in Kahayan Central Forest Management Unit - Iskandar, Beni; Khasanah, Kholifatun; Sari Marlina, (Journal of Sylva Indonesiana, 2025)
In 2015 and 2019, the Central Kahayan Forest Management Unit (FMU) experienced forest fires on peatlands that had significant impacts on ecological, economic, and social aspects. Consequently, it is imperative to devise a comprehensive strategy aimed at the enhancement of a susceptibility map for forest and land fires. This research endeavor seeks to construct a detailed framework that assesses the susceptibility of forested areas and land to fire incidents inside of the Kahayan Central Forest Management Unit (FMU). The frameworking procedure will employ an integrated approach that synergizes the Analytical Hierarchy procedure (AHP) by Geographic Information System (GIS) technologies to achieve a more robust analysis of fire susceptibility. The outcomes showed that there are three classes of forest and land fire susceptibility, namely the unsusceptible class covering 152,760 hectares (41%), the moderately susceptible class covering 150,171 hectares (40%), and the very susceptible class covering 72,585 hectares (19%). The outcomes of this research are anticipated to provide a foundational framework for the effective management and mitigation of forest and land fires inside of the Central Kahayan Forest Management Unit (FMU), thereby aiming to alleviate the adverse impacts associated by such incidents.